An ongoing problem: Rhesus hemolytic disease of the newborn - A decade of experience in a single centre - Cansu Yilmaz Yegit; Beril Yasa; Elmas Zeynep Ince; Tugba Sarac Sivrikoz; Asuman Coban (Pediatrics and Neonatology)
Background: The objectives were to evaluate the descriptive features of newborns with a diagnosis of Rhesus (Rh) hemolytic disease, to determine the morbidity and mortality rates, to evaluate the treatment methods and the factors affecting treatment requirements and clinical outcomes during a ten-year period at a tertiary center. Methods: Newborn infants who had a positive direct Coombs test and/or had a history of intrauterine transfusion (IUT) due to Rh hemolytic disease were included. The data regarding the prenatal, natal and postnatal periods were collected from hospital records. Results: A total of 260 neonates were included of which 51.2% were female. The mean ± standard deviation gestational age was 36.9 ± 2.7 weeks. The rate of preterm birth was 41.2%. Of 257 mothers whose obstetric medical history could be accessed, 87.2% were multigravida, whereas 76.3% were multiparous. Among mothers who had a reliable history of anti-D immunoglobulin prophylaxis (n=191), 51.3% had not received anti-D immunoglobulin prophylaxis in their previous pregnancies. The antenatal transfusion rate was 31.7% and the frequency of hydrops fetalis was 8.8%. While combined exchange transfusion (ET) and phototherapy (PT) was performed in 15.4% of the babies, the majority either needed phototherapy only (51.1%) or no treatment (33.5%). The mortality rate was 3.8 % (n = 10), and nine babies out of these 10 were those with severe hydrops fetalis. Conclusion: This study showed that Rh hemolytic disease is still a major problem in developing countries. Multiple comorbidities may occur in addition to life threatening complications, including hydrops fetalis, anemia and severe hyperbilirubinemia. High rates of multiparity and low rates of anti-D immunoglobulin prophylaxis are potential barriers for the eradication of the disease. It should be remembered that Rh hemolytic disease is a preventable disease in the presence of appropriate antenatal follow-up and care facilities.